Cover crops in coffee management in production (Research, Society and Development, 2022)
Cover crops between rows of coffee contributes to the promotion of a sustainable production. The objective of this work was to evaluate the improvement of the chemical and physical attributes of the soil and coffee production using cover crops between the coffee lines. This study was at Boa Esperança Farm, Serrania – MG. The experimental design consisted of randomized blocks, with 7 treatments and 4 replications: control, no cover plant, with traditional farm management (chemical and mechanical weed control); crotalaria (Crotalária spectablis); cuandu (Cajanus cajan); cowpea (Vigna unguiculata L. Walp.); mix of crotalaria + cuandu + cowpea; Brachiaria brizanta (Urochloa brizantha) and Brachiaria ruzizienses (Urochloa ruzizienses) as cover plants. The data were submitted to analysis of variance by the Scott-Knott test at 5% probability. Results confirm that cover crops promote cycling and nutrient accumulation in the soil, maintain a mild temperature and promoted better moisture maintenance. It also demonstrated that although the population dynamics of weeds have a positive result, only the use of cover crops is not enough for 100% weed control in the coffee crop. Besides, they have a contribution to the development and production of coffee and to reduce the phytonematoid population.